Acceleration of Settlement of Bank Assets and Liabilities in Liquidation by Liquidation Auditor - Junanda, Lalu Riko; Karunia, Lalu Zayen Cipta; Sokarina, Ayudia (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
Bank liquidation is an effort to fulfill all liabilities, both obligations and rights of a factor due to the revocation of a license and the dissolution of a legal entity from the bank. The scope of bank liquidation does not only mean the bank's license being revoked and the legal entity being dissolved, but also the treatment of all rights and obligations of the bank whose license has been revoked. It was recorded that as many as 10 Rural Credit Banks (BPR) in the first semester of 2024 had their business licenses revoked by the Financial Services Authority OJK. After their business licenses were revoked by the OJK, the Deposit Insurance Corporation (LPS) was given a mandate through Law No. 24 of 2004 to resolve failed banks through bank liquidation. One of the bank liquidation processes involves a Public Accounting Firm (KAP) to provide liquidation audit services. The purpose of the liquidation audit is to verify the financial statements prepared by the liquidation team formed by LPS. The community service team had the opportunity to do an internship at KAP. KAP assigned to assist in the liquidation audit process at Bank Under Liquidation (BDL) in Indramayu, West Java. As a result, the liquidation audit team carried out several audit procedures, namely: document vouching, field surveys to debtors, and physical checks of BDL assets. At the reporting stage, the evidence obtained was then used to complete and produce the BDL Net Asset Change Report (LAPAN) which was submitted to the service user, namely LPS.